Predicting and Reinforcing the Critical Buckling Loads of Flexible Corrugated Panels - Chen Wang; Ye Mao; Quan Liu; Siyun Fan; Xing Shen; Jiaying Zhang; Yuying Xia (Machines, 2023)
Corrugated panels are promising in the field of morphing structures due to their high anisotropy. A low stiffness in the morphing direction allows for a reduced actuation force, which provides the benefit of reducing the system weight. However, a low stiffness also leads to reduced critical buckling loads, which makes it easier for corrugated panels to buckle in the morphing process. The conflict between the actuation force and the critical buckling load requires an efficient method to predict the critical buckling load, which can then be applied in a trade-off study to find the optimal design. In the current study, a simplified method to predict the critical buckling load is proposed based on the derivation of equivalent properties. The method is verified using the finite element analysis and applied for the optimisation of corrugated panels. A conceptual design to reinforce corrugated panels is also proposed, which shows a significant increase in the critical buckling load of flexible corrugated panels.